Local Integration Determinants of Upstream and Downstream Firms' Transactions in Six Portuguese Small and Medium-Sized Marketowns - Francisco Diniz (European Regional Science Association (ERSA), 2006)
The first step will be to measure the firms sales and purchases economic impact based on small and medium-sized towns and to calculate their degree of integration into the local economy, comparing the local economic integration of small and medium-sized towns within three types of rural area, in six Portuguese small and medium-sized towns. In this paper a series of Ordinary Least Squares (OLS) Regressions will be presented in such a way as to examine the key characteristics of entity and local environment associated with strong local economic integration, using firm sales and purchases Local Integration Indicators as dependent variables. Each independent variable compared sub-sets of towns and firms to examine the influence of a range of characteristics and distinctions between entities on local economic integration. In order to explain the level of local integration of the sales and purchases of firms, three sets of explanatory variables were taken into consideration. The first set concerns the characteristics of the local context, including country, town type (size and type) and location of the firm within the study area (i.e. in the town centre or hinterland, as previously defined). The second set describes the characteristics of the firm and owner/manager. Besides some usual characteristics (such as firm type, sector, workforce size, age etc), this set also includes indigeneity of the owner/manager, i.e. the length of time that the owner/manager has resided in the study area, and where they moved in from, as well as variables which characterise the firm's technology (proportion of unskilled workers in the workforce, labour productivity and index of intensity in intermediate goods). Finally, a set of 'firm environment' variables were computed. Through these, one will attempt to examine the relationship between the firm (according to its own characteristics) and the integration with local markets of final and intermediate goods and labour.
Keywords: 330